2015
DOI: 10.1509/jppm.14.101
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Restriction in a Total Control Institution: Participatory Action Research in a Maximum Security Prison

Abstract: The marketing and public policy field has a long history of examining consumer decision making under conditions of abundance, but less effort has been dedicated to learning about restrictions to choice, especially as imposed by institutional forces. To help fill this gap in the literature, the authors offer an ethnographic investigation of a maximum security prison conducted over an 18-month period using participatory action research. This environment is a total control institution where depersonalization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…Extant marketing studies explore the discrimination faced by vulnerable customers (e.g. Bone, Christensen and Williams, 2014;Hill, Rapp and Capella, 2015), but few have addressed how vulnerable customers derive value outcomes from their interactions with organisations (Piacentini, Hibbert and Hogg, 2014) . While Larson and Bock (2016) found that mental health customers who were satisfied with their treatment had enhanced well-being, little explanation was provided for how this was achieved through the treatment regime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant marketing studies explore the discrimination faced by vulnerable customers (e.g. Bone, Christensen and Williams, 2014;Hill, Rapp and Capella, 2015), but few have addressed how vulnerable customers derive value outcomes from their interactions with organisations (Piacentini, Hibbert and Hogg, 2014) . While Larson and Bock (2016) found that mental health customers who were satisfied with their treatment had enhanced well-being, little explanation was provided for how this was achieved through the treatment regime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Archetypally, critical performativity is enabled by first determining matters of interest to the research co-participants whether this is the managerial community, non-profit sector or the wider public (cf. Hill et al, 2015). These topics have to speak to the academic competencies of the people involved.…”
Section: Critical Performativitymentioning
confidence: 99%
“…It was pursued with amoral vigour as a function of 'investor pressure' (Oldani, 2016) which had extremely deleterious effects on those who served as guinea pigs for the clinical trial or who later consumed it in the U.S. when the company knew about the side-effects. This focus on profit leads companies to make many questionable decisions and choices (see also Hill et al, 2015;Puchan, 2001).…”
Section: Mccoy 2016)mentioning
confidence: 99%
See 1 more Smart Citation
“…Results suggests that choice, or even the illusion of choice, has affective, cognitive, motivational, behavioral, and physiological benefits (Greenberger, Strasser, Cummings, & Dunham, 1989;Iyengar & Lepper, 2000;Lonsdorf, Ross, Matsuzawa, & Goodall, 2010;Winocur, Moscovitch, & Freedman, 1987;Zukerman, Porac, Lathin, Smith, & Deci, 1978). As a corollary, there is evidence that an external locus of control and lack of free choice can be detrimental (Benassi, Sweeney, & Dufour, 1988;Goodstein, MacKenzie, & Shotland, 1984;Hill, Rapp, Capella, & the Gramercy Gentlemen, 2015;Mineka & Hendersen, 1985;Moore & Cox, 1988;Roddenberry & Renk, 2010;Ruback, Carr, & Hopper, 1986). In fact, human preference for choice is so strong that it does not appear to be contingent on reward outcomes.…”
mentioning
confidence: 99%